Magnesium gasar as a potential monolithic hydrogen absorbent. (6th April 2021) - Boczkal, Grzegorz; Janoska, Malwina; Setman, Daria; Schafler, Erhard; Dlugosz, Piotr; Darlak, Pawel
Abstract: The study focuses on the aspect of using the structure of gasars, i.e. materials with directed open porosity, as a potential hydrogen storage. The structure of the tested gasar is composed of a large number of thin, open tubular pores running through the entire longitudinal section of the sample. This allows hydrogen to easily penetrate into the entire sample volume. The analysis of pore distribution showed that the longest diffusion path needed for full penetration of the metal structure with hydrogen is about L = 50–70 μm, regardless of the external dimensions of the sample. Attempts to hydrogenate the magnesium gasar structure have shown its ability to accumulate hydrogen at a level of 1 wt%. The obtained results were compared with the best result was obtained for the ZK60 alloy after equal channel angular pressing (ECAP) and crushed to a powder form. The result obtained exceeded 4 wt% of hydrogen accumulated in the metal structure, at theoretical 6.9 wt% maximum capacity. A model analysis of the theoretic absorption capacity of pure magnesium was also carried out based on the concentration of vacancies in the metal structure. The theoretical results obtained correlate well with experimental data. Highlights: Strongly developed surface of gasars allows for efficient transfer of hydrogen within the whole volume of material. Production of gasars generates many structural defects similar to SPD methods. Gasars have a great potential as materials for hydrogen absorbents.